Prevalence and Associated Factors of Anxiety and Depression among Teachers at One Private All-Girls Boarding School - พลอยทับทิม กชวรรณ; Chandarasiri, Parichawan; Buathong, Napakkawat; Prasartpornsirichoke, Jirada (Journal of the Psychiatric Association of Thailand, 2021)
Introduction: The trend of anxiety and depression in the world population has increased significantly over the past 10 years and is associated with several factors such as gender, age, underlying disease, substance and alcohol use, education, economic status, workload, etc. “Teacher” is a hard-working profession. It has been found that the prevalence of depression among teachers was very high. Research on mental health problems of teachers in Thailand is still scarce and out of date. In addition, there is no data on the factors of the teachers’ mental health problems in those studies. Objective: To identify the prevalence and the associated factors of anxiety and depression among teachers at one private all-girls boarding school. Methods: This cross-sectional descriptive study collected data from teachers at one private all-girls boarding school from December 2019 to March 2020. The information was collected by self-rated questionnaires including questionnaire of demographic data, socioeconomic factors and job factors, the Thai version of the State-Trait Anxiety Inventory and the Thai version of the Beck Depression Inventory II. Results: There were 114 participants included in the study. The prevalence of low, moderate, and high level of anxiety were 52.6%, 43.9% and 3.5%, respectively. Regarding depression, the prevalence of minimal, mild, and moderate level of depression were 85.1%, 8.8% and 6.1%, respectively. No participants with severe level of depression were found. Factors significantly associated with anxiety were monthly income less than or equal to 30,000 Baht, debt burden greater than 50,000 Baht, Experience in the teaching profession less than or equal to 10 years, dissatisfaction of the time management, dissatisfaction of student behaviors, dissatisfaction with job, dissatisfaction of co-worker relationships, dissatisfaction with the "teacher" career and having moderate to high anxiety trait. Factors significantly associated with depression were childlessness, Experience in the teaching profession less than or equal to 10 years and having moderate to high anxiety trait. Conclusion: “Teacher” is a profession that affects the state of mind. This can be seen from the study that found high prevalence of anxiety (47.4%) and depression (14.9%). The associated factors were socioeconomic problems, job dissatisfaction and anxiety trait. The results of the study will enable the relevant departments to plan further assistance for teachers with anxiety and depression.